INFLUENCE OF PERSONALITY AND SLEEP HYGIENE ON INSOMNIA (REMUNOM, 2025)
Insomnia is a highly prevalent sleep disorder, associated with mood disorders and cognitive impairment. Susceptibility to developing insomnia may be related to personality traits, and neuroticism seems to be implicated in the development of this disorder. Objective: To investigate the influence of the personality trait neuroticism on the relationship between sleep hygiene and insomnia among university students in Brazil. Method: This is an individual, observational, cross-sectional study. An electronic, self-administered questionnaire was used on the Microsoft Forms platform. Sociodemographic aspects, prevalence of anxiety and depressive symptoms, personality traits, sleep quality, and insomnia were addressed. Brazilian university students or those residing in Brazil, aged 18 or older, with access to digital devices, were included. Results: A total of 456 responses to the questionnaire were collected, with the majority being female (84.8%), undergraduate students (79.2%), in the health field (46.8%), and with more than 75% of their course completed. A correlation was found between the dependent variable insomnia and the independent variables anxiety, depression, and stress. An association of insomnia was also observed with the personality trait detachment, marked by avoidance of interpersonal interactions, anhedonia, and limited affective experiences. Insomnia was also associated with certain sleep hygiene habits. Conclusion: The reduction in sleep quality was found to be associated with altered mental health and poor sleep hygiene habits. The study did not find a direct association between increased levels of neuroticism and a worse subjective sleep experience. Further studies are necessary with a sample offering greater sociodemographic diversity.KEYWORDS: Insomnia; Mental Health; Personality; Neuroticism; Sleep Hygiene